2021
DOI: 10.3389/fimmu.2021.660298
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Type-I Interferon for Immediately Available Prophylaxis Against Emerging Respiratory Viral Infections

Abstract: In addition to SARS-CoV-2 and its variants, emerging viruses that cause respiratory viral infections will continue to arise. Increasing evidence suggests a delayed, possibly suppressed, type 1 interferon (IFN-I) response occurs early during COVID-19 and other viral respiratory infections such as SARS and MERS. These observations prompt considering IFN-β as a prophylactic or early intervention for respiratory viral infections. A rationale for developing and testing intranasal interferon beta (IFN-β) as an immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
4
0
2
Order By: Relevance
“…Prophylactic strategies with drugs such as hydroxychloroquine or ivermectin did not show any significant reduction in the risk of SARS-CoV-2 infection [ 7 ]. Other treatments, such as post-exposure type I interferon prophylaxis, are still being evaluated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic strategies with drugs such as hydroxychloroquine or ivermectin did not show any significant reduction in the risk of SARS-CoV-2 infection [ 7 ]. Other treatments, such as post-exposure type I interferon prophylaxis, are still being evaluated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 IFNs administered before a viral infection or post-infection but before the inflammatory response peaks have been shown to offer a high level of protection (Bessiere et al, 2021; Channappanavar et al, 2019; Lee et al, 2021; Sabit et al, 2018; Sodeifian et al, 2022). Several studies even reported the beneficial effect of IFN-α in the treatment of SARS-CoV-2-infected patients (Bhushan et al, 2021; Pandit et al, 2021; Pereda et al, 2020a; Pereda et al, 2020d; Rahmani et al, 2020; Zhou et al, 2020a; Zhou et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, IFN-α and other IFN subtypes, including type III IFN and in particular IFN-λ1, can be considered, either directly or through the administration of drugs inducing IFN or IFN-induced genes. As discussed in detail elsewhere, among the strategies aimed at limiting pandemic viruses spread, the possible use of intranasally administered IFN-I as prophylactic measure for high-risk individuals should be also evaluated [82] .
Fig.
…”
Section: Closing Remarksmentioning
confidence: 99%